PERANAN HUKUM DALAM PENGENDALIAN KORUPSI TERHADAPPEMBANGUNAN EKONOMI DI INDONESIA - Eko Budianto; Tomson Situmeang (INTELIGENSIA MEDIA, 2026)
Corruption is one of the biggest challenges in Indonesia's economic development. Corruption practices not only reduce resource allocation efficiency but also erode public trust in state institutions. This study aims to analyze the role of law in controlling corruption to support sustainable economic development. Using a normative-empirical approach, the study reveals that law plays a significant role in fostering transparency, accountability, and deterrence through strict law enforcement. However, the effectiveness of the law is often hindered by weaknesses in the judicial system and inadequate oversight. Comprehensive legal reform, strengthening of supervisory institutions, and integration of digital technology are needed to enhance efficiency and reduce corruption potential. This study concludes that effective corruption control can significantly contribute to inclusive and sustainable economic growth